Post-processing open-source software for the CBCT monitoring of periapical lesions healing following endodontic treatment: technical report of two cases - Villoria, Eduardo M (Dentomaxillofac Radiol, 2017)
OBJECTIVES: To describe the use of open-source software for the post-processing of CBCT imaging for the assessment of periapical lesions development after endodontic treatment. METHODS: CBCT scans were retrieved from endodontic records of two patients. Three-dimensional virtual models, voxel counting, volumetric measurement (mm(3)) and mean intensity of the periapical lesion were performed with ITK-SNAP v. 3.0 software. Three-dimensional models of the lesions were aligned and overlapped through the MeshLab software, which performed an automatic recording of the anatomical structures, based on the best fit. Qualitative and quantitative analyses of the changes in lesions size after treatment were performed with the 3DMeshMetric software. RESULTS: The ITK-SNAP v. 3.0 showed the smaller value corresponding to the voxel count and the volume of the lesion segmented in yellow, indicating reduction in volume of the lesion after the treatment. A higher value of the mean intensity of the segmented image in yellow was also observed, which suggested new bone formation. Colour mapping and “point value” tool allowed the visualization of the reduction of periapical lesions in several regions. CONCLUSIONS: Researchers and clinicians in the monitoring of endodontic periapical lesions have the opportunity to use open-source software.